2011
DOI: 10.1007/s12264-011-1008-6
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid as a neuroprotective strategy in perinatal hypoxic-ischemic injury

Abstract: Perinatal hypoxia-ischemia remains the single most important cause of brain injury in the newborn, leading to death or lifelong sequelae. Because of the fact that there is still no specific treatment for perinatal brain lesions due to the complexity of neonatal hypoxic-ischemic pathophysiology, the search of new neuroprotective therapies is of great interest.In this regard, therapeutic possibilities of the endocannabinoid system have grown lately. The endocannabinoid system modulates a wide range of physiologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 148 publications
0
13
0
Order By: Relevance
“…The endogenous cannabinoids system (ECS) includes different enzymes responsible for endocannabinoid synthesis, transport and degradation, as well as endocannabinoids and endocannabinoid receptors (Ueda et al 2013). The ECS is important for its regulation over different neurological and physiological processes, that include neural development, synaptic plasticity, reward processing, learning processes, neurogenesis and embryonic cell fate in the developing brain, through the activation of cannabinoid receptors 1 (CB1) and 2 (CB2) (Ahmad and Laviolette 2017;Alonso-Alconada et al 2011;Blanco-Calvo et al 2014;Serrano et al 2012;Schoch et al 2018;Ueda et al 2013;Zhou et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The endogenous cannabinoids system (ECS) includes different enzymes responsible for endocannabinoid synthesis, transport and degradation, as well as endocannabinoids and endocannabinoid receptors (Ueda et al 2013). The ECS is important for its regulation over different neurological and physiological processes, that include neural development, synaptic plasticity, reward processing, learning processes, neurogenesis and embryonic cell fate in the developing brain, through the activation of cannabinoid receptors 1 (CB1) and 2 (CB2) (Ahmad and Laviolette 2017;Alonso-Alconada et al 2011;Blanco-Calvo et al 2014;Serrano et al 2012;Schoch et al 2018;Ueda et al 2013;Zhou et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] This effect was proposed in neonatology as a therapeutic mean in case of asphyxia in the newborn. 27 As a limitation of our study the newborn's endocannabinoid activity remains unclear, because it is not possible to determine whether the measured endocannabinoids are of maternal or fetal origin. However, regardless the origin of the endocannabinoids, they still affect the newborn and may support the fetal transition.…”
Section: Discussionmentioning
confidence: 94%
“…A growing evidence indicates that modulation of the ECS has neuroprotective effects in hypoxia-ischemia [13,25,26]. Regarding AEs that do not bind to CB receptors, it has been demonstrated that OEA administration before ischemic brain injury induces an increase in PPARα expression and reduces infarct volume and brain edema in mice [28].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been previously demonstrated that the ECS plays a neuroprotective role in models of neonatal and adult cerebral ischemia [13,25,26], this effect has not yet been tested in the PA model developed by Bjelke et al [4]. In former works, OEA and PEA have been shown to present neuroprotective effects in adult cerebral ischemia [27,28], but they have not been tested in neonatal hypoxia-ischemia models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation